딥러닝 기법을 이용한 P2P 소셜 대출 채무자 부도 예측모델에 관한 연구 - 이현진(Hyun-Jin Lee) (디지털콘텐츠학회논문지, 2019)
국내외적으로 다양한 P2P 소셜 대출 서비스가 등장하면서 플랫폼 서비스 업자나 투자자 입장에서는 연체나 부도가 발생하지 않을 대출 요청을 찾아서 투자하는 것이 중요하다. 하지만, 대출 요청자의 특성 상 은행에서 대출받는 사람들보다는 높은 연체율을 보이는 것이 사실이다. 따라서, 대출 요청 내용을 분석하여 연체나 부도가 발생하지 않을 대출을 선별하는 것이 중요하다. 본 논문에서는 렌딩 클럽 데이터를 이용하여 딥러닝 기법을 이용한 P2P 소셜 대출 채무자 부도 예측 모델을 개발하였다. 정확도를 높이기 위하여 전체 변수를 사용하고, 학습 속도를 높이기 위하여 계층적 오토 인코더로 특징을 추출하였다. 인공지능 기반 균등 부분 표본 추출로 데이터 클래스를 균일하게 하고, 다층 퍼셉트론을 이용하여 부도 예측을 수행하였다. 렌딩 클럽 데이터에 적용하여 정확도와 정밀도 모두 기존 방법보다 높은 성능을 보이는 것을 확인 할 수 있었다. It is important for platform service providers and investors to find and invest in loan requests that do not cause delinquency or default. However, due to the characteristics of the loan requestor, it is true that the default rate is higher than those who are borrowed from the bank. Therefore, it is important to analyze the contents of the loan request to select the loans for which no delinquency or default will occur. In this paper, we developed a prediction model of P2P social loan debtor 's default using deep learning method for lending club database. We used all parameters to increase the accuracy and extracted features using stacked auto encoder to increase learning speed. Using AI based balanced sub sampling the data class is uniformized and the default prediction is performed using the multi-layer perceptron. As a result of applying it to the lending club database, it was confirmed that both the accuracy and the precision outperforms other classifiers. KCI Citation Count: 4